Face recognition problems for artificial intelligence in case with social medias - Логвінова, К. В. (ХНУРЕ, 2020)
Nowadays, a certain kind of experience in the era of information technology and information technology, the problem of creating “smart” technology is especially urgent. On the “smart” technologies on the current day, you can rozumіti cars with programs of any complexity, all kinds of pralny machines, especially the robbery mode before the robots, which can make pictures and cherubs by co-workers.